PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU KEJAHATAN EKSPLOITASI SEKSUAL KOMERSIAL ANAK (STUDI PUTUSAN PENGADILAN NEGERI) - Eva Syahfitri Nasution; Syafruddin Kalo; Muhammad Hamdan; Edy Ikhsan (USU LAW JOURNAL, 2015)
ABSTRACT Children are a gift from God the Almighty who always has to be kept for, because they have rights as human beings that must be held. Nowadays, there are many problems that threaten children, but commercial sexual exploitation of children is the worst problem for children. In commercial sexual exploitation of children, child is not only used as a sexual object, but also served as a commercial object to obtain reward or benefit. The forms of commercial sexual exploitation of children in Indonesia are children prostitution, child pornography and trafficking of children for sexual purposes. The law governing the crime of commercial sexual exploitation of children in Indonesia is Law 23 of the year 2002 on Child Protection, Law 21 of the year 2007 on The Eradication of The Criminal Act of Trafficking In Person and Law 44 of the year 2008 on Pornography. Criminal liability of commercial sexual exploitation of children offenders be held accountable if the perpetrator has met the elements of criminal liability. In the law enforcement related the crime in the verdict, the Judge consider based on the elements of criminal liability and also apply the law in accordance with the facts revealed in the trial. Keywords : criminal liability, sexual exploitation, children